Essential maps for the lost eaudiobook - Caletti, Deb (Tantor Audio, 2016)
There are many ways to be lost. Sometimes people want to be lost. Madison-Mads to everyone who knows her-is trying her best to escape herself during one last summer away from a mother who needs more from her than she can give, and from a future that has been decided by everyone but her. Sometimes the lost do the unimaginable, like the woman, the body, Mads collides with in the middle of the water on a traumatic morning that changes everything. And sometimes the lost are the ones left behind, like the son of the woman in the water, Billy Youngwolf Floyd. Billy is struggling to find his way through each day in the shadow of grief. His one comfort is the map he carries in his pocket, out of his favorite book, The Mixed-Up Files of Mrs. Basil E. Frankweiler. When three lives (and one special, shared book) collide, strange things happen. Things like questions and coincidences and secrets, lots of secrets. Things like falling in love. But can two lost people telling so many lies find their way through tragedy to each other and to solid ground?